Enhancing 21 St-Cetury Skills Through Project-Based Learning: Isights from Vocational Education in Egypt - Farhan Hanif; Abdurrahman Abdurrahman (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research examines the use of Project-Based Learning (PBL) as a strategy to develop practical skills among secondary school students in Egypt. Recognized as a modern and innovative teaching method, PBL actively involves students in the learning process, enabling them to apply theoretical concepts to real-world situations. Using a qualitative research approach, this study focuses on case studies of Egyptian secondary schools that have implemented PBL in their curricula. Data collection methods included interviews with teachers and students, classroom observations, and analysis of student projects, lesson plans, and curriculum documents. The findings indicate that PBL significantly improves the learning experience by motivating students and fostering active engagement. Students involved in group projects demonstrated better comprehension of academic material, stronger critical thinking, increased confidence in presentations, and improved collaboration skills. However, challenges such as insufficient resources, limited teacher training, and an exam-oriented curriculum pose barriers to PBL’s success. Teachers often struggle with time management for project-based activities, and the effectiveness of PBL heavily relies on their ability to guide and facilitate learning. To overcome these issues, the study recommends enhancing teacher training programs, adopting more flexible education policies, and utilizing technology to diversify and enrich project-based activities. By optimizing resources and increasing awareness of PBL’s advantages, Egypt’s education system can better equip students with essential 21st-century skills. Penelitian ini mengkaji penggunaan strategi Project-Based Learning (PBL) untuk meningkatkan keterampilan praktis siswa sekolah menengah di Mesir. Diakui sebagai metode pengajaran yang inovatif, PBL secara aktif melibatkan siswa dalam proses pembelajaran dan memungkinkan mereka menerapkan konsep teoretis ke dalam situasi nyata. Pendekatan kualitatif digunakan dalam penelitian ini, dengan fokus pada studi kasus sekolah menengah di Mesir yang telah mengintegrasikan PBL dalam kurikulumnya. Data dikumpulkan melalui wawancara mendalam dengan guru dan siswa, observasi kelas, serta analisis proyek siswa, dokumen kurikulum, dan rencana pembelajaran. Hasil penelitian menunjukkan bahwa PBL secara signifikan meningkatkan pengalaman belajar, memotivasi siswa, dan mendorong keterlibatan aktif. Siswa yang terlibat dalam proyek kelompok menunjukkan pemahaman akademik yang lebih baik, kemampuan berpikir kritis yang lebih kuat, kepercayaan diri dalam presentasi, dan keterampilan kerja sama yang lebih baik. Namun, terdapat tantangan seperti keterbatasan sumber daya, kurangnya pelatihan guru, dan kurikulum yang berorientasi pada ujian. Guru sering menghadapi kesulitan dalam mengelola waktu untuk kegiatan berbasis proyek, dan keberhasilan PBL sangat bergantung pada kemampuan mereka dalam memfasilitasi pembelajaran. Untuk mengatasi hambatan ini, penelitian merekomendasikan peningkatan program pelatihan guru, adopsi kebijakan pendidikan yang lebih fleksibel, dan pemanfaatan teknologi untuk memperkaya dan mendiversifikasi kegiatan berbasis proyek. Dengan mengoptimalkan sumber daya yang ada dan meningkatkan kesadaran akan manfaat PBL, sistem pendidikan Mesir dapat lebih mempersiapkan siswa dengan keterampilan abad ke-21 yang esensial.